The Case of anti-HCV Negative Chronic Hepatitis C - A. L. Rossina; S. B. Chuelov; A. V. Smirnov (Детские инфекции (Москва), 2015)
The paper gives a brief literary reference relating to contemporary aspects of serological diagnosis of hepatitis C, and understands a clinical example of chronic hepatitis C in a child with acute lymphoblastic leukemia, with the absence of circulating antibodies to HCV classes M, and G for almost 2 years.